2018
DOI: 10.1051/matecconf/201815403010
|View full text |Cite
|
Sign up to set email alerts
|

Clustering on Twitter: case study Twitter account of higher education institution in Indonesia

Abstract: Abstract. Recently, higher education institutions have been using Twitter as one of tools to enhance their communication network. This paper aims to cluster Twitter data retrieved from the official Twitter account of higher education institutions in Indonesia. We expect to obtain a valuable information from the tweet posted. Furthermore, we use Twitter's hashtag as a basis of clustering. We collect data from n=10 institutions that have an official account on Twitter. The Affinity Propagation algorithm was empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In light of these research gaps, this study posits the following research questions focusing on the MCG-based e-WOM: This study proposes to extract tweet characteristics from Twitter data posted by the official Twitter accounts of Thai commercial banks, to identify tweet intents from those tweets, to compare the association of intents between RT tweets and FAV tweets, to find the strategies of tweet intents, and to explore the intent strategies together with other characteristics to predict RT or FAV on each tweet, using data-mining techniques (association rules, clustering, and classification). Hamzah and Hidayatullah (2018) tried to cluster Twitter data from the official account of higher education institutions based on hashtags. The results showed that Indonesian higher education institutions mostly used Twitter to post general information, news, agenda, announcement, information for new students, and achievements.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these research gaps, this study posits the following research questions focusing on the MCG-based e-WOM: This study proposes to extract tweet characteristics from Twitter data posted by the official Twitter accounts of Thai commercial banks, to identify tweet intents from those tweets, to compare the association of intents between RT tweets and FAV tweets, to find the strategies of tweet intents, and to explore the intent strategies together with other characteristics to predict RT or FAV on each tweet, using data-mining techniques (association rules, clustering, and classification). Hamzah and Hidayatullah (2018) tried to cluster Twitter data from the official account of higher education institutions based on hashtags. The results showed that Indonesian higher education institutions mostly used Twitter to post general information, news, agenda, announcement, information for new students, and achievements.…”
Section: Introductionmentioning
confidence: 99%